Virtual reassembly and completion of a fragmentary drinking vessel - Despoina Tsiafaki; Anestis Koutsoudis; Fotis Arnaoutoglou; Natasa Michailidou (Virtual Archaeology Review)
A  key  issue  in  the  study  of  cultural  assets  is theiroften  fragmentary  condition.  This  causes  serious  problems  and questions regarding theirstudy and presentation. Pottery fragments are the most numerous findings in every excavation. Furthermore, pottery plays an essential role for the reconstruction of the past, since it providesinformation for all aspects of  life  (private,  public,  religion,  death,  economy,  society,  trade,etc.). Therefore,a  thorough  study  and  presentation  of pottery fragments contribute to a better knowledge of the past.The focus of this work is the visualisation of an ancient Greek  drinking  vase,  a kantharos,  which  was  unearthed  during  the  excavations  at  the  settlement  of  Karabournaki (ancient Therme) in the area of Thessaloniki (Greece). It dates to the Archaic period (7th-6thc. B.C.) and it was found in fragments  among  the  settlement's  architectural  remains.  The  vase  is  of  great  archaeological  significance  due  to  its peculiarities  in  terms  of  shape,  decoration  and  function. Therefore,its  digital  completion  and  3D  reconstruction  willcontribute to its betterstudy and scholarly publication along with a general contribution to the field of pottery studies.We discuss  on  the  3D  digitisation  of  the kantharosfragments  that  werebased  onStructure from Motion/Multiple  View Stereovision  (SfM/MVS)  and  a  custom  automated  data  collection  system.  A  detailed  description  of  the  digitisation pipeline is given along with details related to the quality of the 3D digital replicas of the sherds. Furthermore, we presentour  manual  virtual  reassembly  and  reconstruction  pipelineof  the kantharosby  describing  the  challenges,  issues  and ambiguities discovered while analysing the geometrical features of each sherd. A number of photorealistic reconstruction visualisations  of  the  artefact  are  presented  in  order  to  question  the  applicability  of  the  solution  for  the  actual reconstruction